Studi Literatur Terkait Analisis Perilaku Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Tenaga Kesehatan Saat Wabah Pandemi Corona Virus (Covid-19) - E, Selina Alta; Widjasena, Baju; Wahyuni, Ida (Jurnal Ilmiah Mahasiswa, 2020)
In early 2020, an epidemic emerged caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), namely Coronavirus Disease 2019 (COVID-19). It was recorded that 989 health workers died from COVID-19 worldwide or 0.37% (989 out of 270,426). During the COVID-19 pandemic, PPE wasn’t only used by healthcare workers, but also was used by the public. Such conditions force some healthcare workers to saving on the use of PPE or use PPE improperly. This makes them become a vulnerable group to be infected. Aim: The purpose of this study was to analyse the compliance behaviour of health workers using PPE during the COVID-19 pandemic. Method:The method used in this research is a literature review, conducted online through several trusted websites such as ScienceDirect, ProQuest, Cambridge Core, Scopus, PubMed, EBSCO Host and Google Scholar. This study analysed 14 international articles that were selected according to the criteria by PRISMA's protocol. Results: Many healthcare workers haven’t complied with using PPE. By using L. Green's behaviour theory, several factors influence this behaviour. There’s a perception of the experience of healthcare workers about the perceived discomfort due to inappropriate PPE’s design. Also known that some healthcare workers who haven’t received training on the use of PPE. Those who have certain respiratory conditions will be aware that they are in a high risk of being exposed to the virus. Therefore, they will be more aware to use PPE. Besides, it was also found that natural environmental conditions can become obstacles in health behaviour.